Teaching STEM outdoors : activities for young children - Selly, Patty Born (Redleaf Press, 2017)
"Connect nature play, outdoor experiences, and STEM learning for young children with activities, real-life examples, and educator resources. Nurture young children's innate tendencies toward exploration, sensory stimulation, and STEM learning when you connect outdoor learning and STEM curriculum. Discover the developmental benefits of outdoor learning and how the rich diversity of settings and materials of nature gives rise to questions and inquiry for deeper learning. Full of activities, examples, and resources to take the fun of STEM outside, this book will help teachers articulate connections between nature play, outdoor experiences, and STEM learning in young children. Use STEM and nature-based learning to nurture children's curiosity and exploration of the world. Patty Born Selly is an assistant professor of environmental education and STEM at Hamline University. She previously served as the executive director of the National Center for STEM Elementary Education at St. Catherine University. Selly has over twenty years of experience in early childhood education, has written two books, and regularly consults other educators on science and nature education approaches for young children"--